Effectiveness of insecticide-treated bednets in malaria prevention in Haiti: a case-control study. Issue 1 (January 2017) - Steinhardt, Laura C; Jean, Yvan St; Impoinvil, Daniel; Mace, Kimberly E; Wiegand, Ryan; Huber, Curtis S; Alexandre, Jean Semé Fils; Frederick, Joseph; Nkurunziza, Emery; Jean, Samuel; Wheeler, Brian; Dotson, Ellen; et al.
Summary: Background: Insecticide-treated bednets (ITNs) are effective in preventing malaria where vectors primarily bite indoors and late at night, but their effectiveness is uncertain where vectors bite outdoors and earlier in the evening. We studied the effectiveness of ITNs following a mass distribution in Haiti from May to September, 2012, where the Anopheles albimanus vector bites primarily outdoors and often when people are awake. Methods: In this case-control study, we enrolled febrile patients presenting to outpatient departments at 17 health facilities throughout Haiti from Sept 4, 2012, to Feb 27, 2014, who were tested with malaria rapid diagnostic tests (RDTs), and administered questionnaires on ITN use and other risk factors. Cases were defined by positive RDT and controls were febrile patients from the same clinic with a negative RDT. Our primary analysis retrospectively matched cases and controls by age, sex, location, and date, and used conditional logistic regression on the matched sample. A sensitivity analysis used propensity scores to match patients on ITN use propensity and analyse malaria among ITN users and non-users. Additional ITN bioefficacy and entomological data were collected. Findings: We enrolled 9317 patients, including 378 (4%) RDT-positive cases. 1202 (13%) patients reported ITN use. Post-hoc matching of cases and controls yielded 362 cases and 1201 matched controls, 19% (333) of whom reported consistent campaign net use. After using propensity scores to match on consistent campaign ITN use, 2298 patients, including 138 (7%) RDT-positive cases, were included: 1149 consistent campaign ITN users and 1149 non-consistent campaign ITN users. Both analyses revealed that ITNs did not significantly protect against clinical malaria (odds ratio [OR]=0·95, 95% CI 0·68–1·32, p=0·745 for case-control analysis; OR=0·95, 95% CI 0·45–1·97, p=0·884 for propensity score analysis). ITN and entomological data indicated good ITN physical integrity and bioefficacy, and no permethrin resistance among local mosquitoes. Interpretation: We found no evidence that mass ITN campaigns reduce clinical malaria in this observational study in Haiti; alternative malaria control strategies should be prioritised. Funding: The Global Fund to Fight AIDS, Tuberculosis, and Malaria, and the US-based Centers for Disease Control and Prevention (CDC).